2020
DOI: 10.25157/wa.v7i1.3108
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Latihan Interval Training Dengan Running Circuit Terhadap Peningkatan Vo2max

Abstract: This study aims to determine how much influence the interval training and running circuit training has on Vo2max improvement. Following the objectives of the study above, the authors use the method of pre-experiment with "Pre Test Post Test Experiment Design". The population of this research is the students of the Running Loka Ciamis Community, Totaling 20 participants. The research instrument used to collect data was a Bleep test. Based on data analysis using SPSS series 24, the results of data processing as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
4
0
9
Order By: Relevance
“…The sample of this research is the goalkeeper of SSB Gumarang as many as 5 people. This research method is experimental research (Rustiawan, 2020); (Ramadani et al, 2021). The independent variable in this study is the variation of reaction training and the dependent variable in this study is the result of the goalkeeper's reaction speed.…”
Section: Figure 1 Histogram Of the Goalkeeper Initial Ability Visual ...mentioning
confidence: 99%
“…The sample of this research is the goalkeeper of SSB Gumarang as many as 5 people. This research method is experimental research (Rustiawan, 2020); (Ramadani et al, 2021). The independent variable in this study is the variation of reaction training and the dependent variable in this study is the result of the goalkeeper's reaction speed.…”
Section: Figure 1 Histogram Of the Goalkeeper Initial Ability Visual ...mentioning
confidence: 99%
“…Technology in achievement sports is used by coaches and athletes to support the training process to the maximum. Through the development of appropriate training technology, it is hoped that the quality of athletes (physical, technical, tactical and mental) can increase so that maximum performance is achieved (Rustiawan, 2020). When the researchers made observations for 1 month, it was found that there were no supporting facilities for training at the club, so far they only did regular exercises or without tools to support training in volleyball playing techniques, especially passing techniques.…”
Section: Development Of Bounce Wall Training Aids To Practice Passing...mentioning
confidence: 99%
“…VO2Max adalah kemampuan seseorang untuk melakukan suatu aktivitas dalam waktu tertentu tanpa mengalami kelelahan yang berarti, dan orang tersebut masih mempunyai cadangan tenaga untuk melakukan suatu aktivitas (Juniardi, Atiq, & Purnomo, 2016). Ada beberapa hal yang harus di perhatikan untuk melatih VO2Max, yaitu, latihan harus menggunakan otot-otot besar secara intensif dalam durasi yang cukup lama (Rustiawan, 2020). Beberapa Faktor yang mempengaruhi nilai VO2Max antara lain, jenis kelamin, suhu dan keadaan latihan (Juniardi et al, 2016 Berdasarkan data di atas menunjukkan bahwa perlu adanya usaha meningkatkan kemampuan VO2Max pada anggota komunitas sepeda Pit Merasi.…”
Section: Pendahuluanunclassified